(untitled) (International Journal of Physiotherapy, 2022)
Background: Often, cricket is stated as an aerobic sport; however, when broken down, the game is played by the players performing at various speeds and intensities-jumping, sprinting, catching, diving, majority of the play is in intervals, and the activity does not last for extended periods (e.g., batting, bowling, fielding, wicket keeping, making a run). The study aims to determine the association between explosive power & endurance in state-level cricket players. Previous studies have investigated physical performances concerning injury incidence and prevention. In this study, physical aspects such as power and aerobic and anaerobic fitness shall be considered. Also, due to the lack of evidence and studies in this literature, it is essential to find an association between the explosive power and endurance among cricket players at the state level. Methods: The present study was conducted in Faridabad, with 100 male state-level cricketers from different cricket academies included in the study. Subjects in the age group of 16-23 were taken in the study. Screening and assessment protocol was followed to select participants. Performance tests were measured. Explosive power with vertical jump test and endurance using yo-yo intermittent recovery test level. Results: The study results revealed that the correlation between explosive power and VO2 max was .237* and was significant at .017. Conclusion: The study concluded that explosive power is positively correlated with the V02 max levels in state-level cricketers.